Planning for Retirement - Tachasermsukkul, Lissara (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
In addition to playing a significant role in the economic system and development of the country, savings are also a source of future security for most households. During the past few years the overall savings situation of Thais has developed in a non-positive direction. A large number of Thai households still have no savings. Only a few Thais are aware of the need for retirement planning and have knowledge to do it. Most do not make any financial plan for their retirement or start their saving plan too late to allow adequate funds for their expenses after retirement. Financial planning for retirement consists of two parts. The first part is Savings, the amount required for spending after retirement to the end of life. The second part is Investment. This is to gain appropriate returns from the savings by making investment in various financial instruments. The saved fund should be allocated in the form of a portfolio of several financial instruments deemed appropriate based on personal preferences in order to diversify risk. For long-term investment, ownership in common stock often provides a high rate of returns in compensation for the higher risks. The retirement savings for a 10-30 years period in the future are enough to allocate a part of this fund for ordinary shares of value-stock known to pay consistent and high dividends.